3D printable 'just-add-water glass and water' geopolymer-an experimental research based on extrusion-based 3D printing practices. Issue 4 (March 2020) - Yin, Xiaohong; Liu, Kaiyuan; Zheng, Shuyi; Zhuang, Kunde; Wang, Xiaodong; Fang, Yuan; Ding, Zhu
Abstract: The application of 3D printing technique has been bringing construction to a new stage. Development of suitable materials and suitable printing process of printable mixtures are very important issues. The present study aims to understand the strategies for the application of 'just-add-water glass and water' geopolymer in extrusion-based 3D printing. The 3D printing practice showed that the satisfactory printing quality, including extrudability, shape retainability, and buildability, can be achieved by adjusting water-to-binder ratio and gap time between layers for the 'just-add-water glass and water' geopolymer in fly ash – slag binary system.